Altered cobalamin metabolism in Escherichia coli btuR mutants affects btuB gene regulation. - Lundrigan, M D (1989)
Synthesis of the Escherichia coli outer membrane protein BtuB, which mediates the binding and transport of vitamin B12, is repressed when cells are grown in the presence of vitamin B12. Expression of btuB-lacZ fusions was also found to be repressed, and selection for constitutive production of beta-galactosidase in the presence of vitamin B12 yielded mutations at btuR. The btuR locus, at 27.9 min on the chromosome map, was isolated on a 952-base-pair EcoRV fragment, and its nucleotide sequence was determined. The BtuR protein was identified in maxicells as a 22,000-dalton polypeptide, as predicted from the nucleotide sequence. Strains mutant at btuR had negligible pools of adenosylcobalamin but did convert vitamin B12 into other derivatives. Although btuB expression in a btuR strain could not be repressed by cyano- or methylcobalamin, it was repressed by adenosylcobalamin. Growth on ethanolamine as the sole nitrogen source requires adenosylcobalamin. btuR mutants grew on ethanolamine but were affected in the length of the lag period before initiation of growth, which suggested that an alternative route for adenosylcobalamin synthesis might exist. No mutations were found that conferred constitutive btuB expression in the presence of adenosylcobalamin. Other genes near btuR may also be involved in cobalamin metabolism, as suggested from the complementation behavior of strains generated by excision of the Tn10 element in btuR. These results indicated that the btuR product is involved in the metabolism of adenosylcobalamin and that this cofactor, or some derivative, controls btuB expression.